Penerapan Metode Demonstrasi dalam Pembelajaran Fiqih untuk Meningkatkan Pemahaman Tata Cara Ibadah di Madrasah Ibtidaiyah - Burhanudin Burhanudin (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Fiqih learning at the Madrasah Ibtidaiyah level plays a crucial role in shaping students’ understanding of proper worship practices in accordance with Islamic law. However, in practice, fiqih instruction is often delivered through verbal and teacher-centered approaches, causing students to focus more on memorization rather than meaningful understanding and correct application. This study aims to examine the implementation of the demonstration method in fiqih learning as an effort to improve students’ understanding of worship procedures, particularly in practical materials such as ablution, prayer, and other daily acts of worship in Madrasah Ibtidaiyah. The demonstration method is considered appropriate because it allows students to directly observe the processes and stages of worship practices, making learning more concrete, contextual, and meaningful. The findings indicate that the application of the demonstration method effectively enhances both conceptual and practical understanding of students, increases learning motivation, and minimizes errors in performing worship. Students not only comprehend the sequences and recitations of worship but are also able to practice them correctly in accordance with fiqih principles. Therefore, the demonstration method can serve as an effective learning approach in fiqih instruction at the Madrasah Ibtidaiyah level to develop a comprehensive understanding of worship that integrates cognitive, affective, and psychomotor aspects.